2019
DOI: 10.18502/keg.v1i2.4435
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Precipitated CaCO3 from Ankerite Prepared by Bubbling Method

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The roughness parameters R q and R a was 0.83 and 0.48 nm, respectively. The dimension of CD particle depends on the temperature and processing time 36 and the results showed both the parameters were optimum for the formation of finer particles, in the present study.…”
Section: Morphological Characteristicssupporting
confidence: 61%
“…The roughness parameters R q and R a was 0.83 and 0.48 nm, respectively. The dimension of CD particle depends on the temperature and processing time 36 and the results showed both the parameters were optimum for the formation of finer particles, in the present study.…”
Section: Morphological Characteristicssupporting
confidence: 61%
“…Form FTIR qualitative analysis, and by comparing our results with other studies, the obtained vibration bonds values are in good agreement with results carried out in the literature [45,46,47] which indicates that the most bands are attributed to quartz and calcite. Fig.…”
Section: Fourier-transform Infrared (Ftir) Analysissupporting
confidence: 91%
“…3 indicate the presence of quartz in all rock samples. The characteristic peaks between 1081.85-1096.83 cm −1 and 2357.08-2361.79 cm −1 indicating the emergence of calcite in the whole samples except OH7 the last peaks were absent [45,48]. The element concentrations obtained for the seven sandstones (OH1-OH7) are summarized in the Table 2.…”
Section: Fourier-transform Infrared (Ftir) Analysismentioning
confidence: 99%
“…For the former, the bands at ca. 700, 900 and 1400 cm − 1 attributed to inorganic carbonate, were noted (Munawaroh et al 2018). That indicated that calcium carbonate, i.e.…”
Section: Prepared Acrylic Psamentioning
confidence: 92%